Performance of a crossed exponentially tapered slot antenna for UWB systems - Costa, J. R.; Medeiros, C. R.; Fernandes, C. A. (IEEE Transactions on Antennas and Propagation, 2009)
A compact printed antenna is described that exhibits adequate transient performance for ultrawideband (UWB) applications and it is further adequate for polarization diversity schemes. The antenna is based on an original combination of two crossed exponentially tapered slots plus a star-shaped slot to produce a stable radiation pattern with very stable polarization over the 3.1–10.6 GHz FCC assigned band. Results are confirmed with measurements. Figures of merit like output pulse fidelity and time window containing 90% of the transmitted energy are analyzed over the entire solid angle and showed to remain quite stable, in line with envisaged UWB system requirements. Compact dual-antenna arrangements are also analyzed in view of potential use for UWB multiple-input–multiple-output implementations.